Multinational business finance - Eiteman, David K.; Stonehill, Arthur I.; Moffett, Michael H. (New York : Pearson, 2022)
'One of the first and leading textbooks for multinational business finance, discussing cutting edge topics of the day'--
Revised edition of the authors's Multinational business finance, [2019]
Includes bibliographical references and index.
Keywords: International business enterprises -- Finance